The Development of School to the Gold Medal Health Promoting School: The Success Lesson of 3 Schools - Chansawang, Wannee; Jittanoon, Piyanuch; Saksorngmuang, Pimpisa (Journal of Health Science of Thailand, 2018)
This qualitative study was aimed at determining the development process, learning process, and factors to the success of the development of the health promoting school. Three gold medal health promoting schools were purposively selected from the primary schools under the office of the Basic Education Commission, the Department of Local Administration, and the Office of the Private Education Commission. Key informants were the health promoting school committees. Data were collected during November 2007 to January 2008 using focus group, in-depth interview and document review. Methodological triangulation was used to validate data. Data were analyzed using content analysis. Findings revealed that the principles used to develop the health promoting school were learning prior to development and using a quality circle. Major features of the development were 1) pupil focusing, idea sharing, un-implemented activity starting and doing, previous job 2) improving, teacher acting, pupil participating, parent and community supporting, and 3) checking, monitoring and evaluating. Lessons that schools have learned from the development of the health promoting school were 1) school development process using a quality circle 2) previous job quality improvement 3) knowledge related to health promoting school and 4) health care knowledge. Factors to the success of the development of the health promoting school were 1) contributing factors, for example, characters of school administrators, school health teachers, teachers, and the awareness of administrators, teachers and pupils; 2) enabling factors, for example, pupil center goal, understanding and awareness raising, intersectoral collaboration building, work planning and monitoring; and 3) supporting factors, for example, the support from administrators, the participation of teachers, pupils and parents as well as the support of communities and related organizations.